Manajemen strategi berbasis teknologi informasi pada bank syariah di era revolusi industri 4.0 - Aqil, Bima Labibul (Maliki Interdisciplinary Journal, 2025)
In the era of the Industrial Revolution 4.0, information technology plays a crucial role in supporting the competitive advantage of financial institutions, including Islamic banks. This article discusses how information technology-based strategic management can be implemented by Islamic banks, analyzing opportunities, challenges, and practical recommendations. The research method utilizes literature review and conceptual analysis. The analysis shows that the integration of technologies such as mobile banking, big data, blockchain, and artificial intelligence (AI) can strengthen the strategic capabilities of Islamic banks, along with managing cybersecurity risks and Sharia compliance. This article also offers an adaptive IT strategic management model to enable Islamic banks to grow and compete in the digital era.